Trucking Stones, Quarry, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A picture of labourers loading stones onto a trolley of railway tracks with one man on top the filled trolley.
Colour; Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Quarries and quarrying